Psychosocial effects of the economic crisis due to the Covid-19 pandemic in the costa rican rural tourism. Period of march to october of 2020 - Jiménez Portilla, Fabián (2023)
The psychosocial effects on micro-enterprise workers of the Costa Rican rural tourism, generated by the economic crisis triggered by the pandemic were characterized. An experimentation of stress and anxiety levels influenced from the emergence of this phenomenon, without deteriorating the overall health of people was found. The approach was mixed, and the instrumental application was with a sample from Vázquez de Coronado and Turrialba. The quantitative perspective used the Lovibond and Lovibond DASS-21 questionnaire adapted by Molina and Salazar (2011), the qualitative portion used a semi-structured interview based on the CASIC Profile proposed by Slaikeu (1984) and the coping strategies of Lazarus and Folkman cited by Perez and Rodriguez (2011). Financial uncertainty has impacted the social, cognitive and affective spheres. There are also positive effects, the interpersonal dimension has generated essential assistance with family support, resulting in a lower impact on mental health.